2016
DOI: 10.1103/physrevb.93.184201
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cross correlations on interdiffusion in Al-rich Al-Ni melts

Abstract: The relation of self-and interdiffusion in a liquid metal, particularly the influence of cross correlations at low concentrations, is studied experimentally. Accurate interdiffusion data are obtained by a combination of x-ray radiography with the shear-cell method on the ground and on the sounding rocket MAPHEUS under microgravity conditions. Self-diffusion coefficients, measured by quasielastic neutron scattering, increase with decreasing Ni concentration, whereas interdiffusion coefficients are about constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
4
22
0
Order By: Relevance
“…Using a linear shear-cell technique even materials that sediment on melting or that show largely different melting and liquidus temperatures can be handled [29,30]. The shear-cell was successfully operated aboard the DLR sounding rocket MAPHEUS-4 in the MIDAS-M setup investigating the influence on cross correlations on interdiffusion in Al-rich Al-Ni alloys [31]. By implementing a newly developed ultra-high temperature shear-cell chemical diffusion in binary Al-Ti and Si-Ge alloys will be investigated aboard MAXUS-9 in spring 2017 using the XRMON-DIFF MAXUS-9 setup.…”
Section: Maxus 9: Diffusion In Liquid Metalsmentioning
confidence: 99%
“…Using a linear shear-cell technique even materials that sediment on melting or that show largely different melting and liquidus temperatures can be handled [29,30]. The shear-cell was successfully operated aboard the DLR sounding rocket MAPHEUS-4 in the MIDAS-M setup investigating the influence on cross correlations on interdiffusion in Al-rich Al-Ni alloys [31]. By implementing a newly developed ultra-high temperature shear-cell chemical diffusion in binary Al-Ti and Si-Ge alloys will be investigated aboard MAXUS-9 in spring 2017 using the XRMON-DIFF MAXUS-9 setup.…”
Section: Maxus 9: Diffusion In Liquid Metalsmentioning
confidence: 99%
“…By the still sharp difference in contrast at the separation line it can be concluded that no major shear-convection occurred. This is due to the slower shear-speed chosen with respect to an earlier measurement on Al-Ni alloys aboard MAPHEUS-4 16 . In Fig.…”
Section: B Chemical Diffusion Linear Shear-cellmentioning
confidence: 86%
“…In order to demonstrate the capability of this facility compared with previous reports from ground experiments 15,23 and a sounding rocket experiment 16 the right capillary which showed a bubble only towards the This is the author's peer reviewed, accepted manuscript. However, the online version of record will be different from this version once it has been copyedited and typeset.…”
Section: Please Cite This Article Asmentioning
confidence: 99%
See 2 more Smart Citations